Uniform distribution in the n-dimensional torus - Misevičius, Gintautas; Kryžienė, Birutė (Lietuvos matematikos rinkinys, 2010)
Limit distribution of endomorphisms of the n-dimensional torus is examined. The obtained result generalizes earlier results of the authors.